Belle Cora [large type] - Margulies, Phillip, 1952- (Thorndike Press large print core series., 2014)
Upon her death in 1919, Mrs. Francis Anderson, a wealthy and powerful dowager in San Francisco society, leaves behind a scandalous memoir revealing her former life as a prostitute and madame. Born Arabella Goodwin to a rich and respected abolitionist family in New York City, she is suddenly orphaned at age nine and shipped off with her beloved youngest brother, Lewis, to live with her aunt and uncle on their hardscrabble farm. When her nemesis -- her cousin Agnes -- engineers Belle's downfall, Belle returns to the city of her youth where she puts her beauty and good-breeding to use, garnering the power and wealth to reclaim what has been taken from her and proving herself a distinctly American heroine: assertive, loyal, vengeful, and unapologetic.